Interactive Media Development Based Macromedia Flash 8 on Themeliving Matter of Primary Class IV - Reffiane, Fine; Bayutama, Laksa (International Journal of Active Learning, 2019)
This study aims to determine the validity and practicality ofFlash-basedinteractive media Macromedia 8 on the theme of care for life mahkhluk Elementary School fourth grade. This research using research methodologies Research and Development (R & D). Steps to develop interactive media-based Macromedia Flash 8 using ADDIE model development procedure (Analysis, Design, Development, Implementation. andEvaluation).The validity of the media obtained from the results of expert validation consisted of three experts and three experts media material. The results obtained from the first media expert 97.5%, 97.5% II media experts and media experts III 100%. Results obtained from the subject matter experts I 98.33% 98.33% Second material experts and subject matter experts 96.66%. The average results obtained from the three media specialists and subject matter experts 98.33% 97.77% criteria